Evaluation of Bacterial Contamination in Dressed Chickens in Lusaka Abattoirs - Prudence Mpundu; Prudence Mpundu; Allan Rabson Mbewe; John Bwalya Muma; Jessy Zgambo; Musso Munyeme (Frontiers Media S.A., 2019)
Objective: The aim of this study was to evaluate bacterial contamination and the risk factors associated with contamination of poultry during processing. Despite the rapid growth of the poultry industry, the presence of high levels of pathogenic bacteria contaminants, such as Escherichia coli and Salmonella, pose serious public health concerns in dressed chickens. These infections negatively affect the product's shelf life.Methods: A cross sectional design was used to study two main poultry abattoirs in Lusaka. The processing line was used to collect biological samples along with the acquisition of risk-associated data using a structured questionnaire. Data collected both from biological sources and the risk analysis were entered into Excel and analysed in STATA version 14 for windows.Results:Escherichia coli and Salmonella contamination was detected in 70 and 2.5% of the selected dressed chickens (n = 80), respectively. The number of total coliforms and Escherichia coli were observed to be significantly higher in samples from washed carcasses than pre-washed carcasses (65 and 35%, respectively). In addition, this study revealed that among the anthropogenic and exposure risk factors, bacterial contamination levels resulted mainly from a lack of hygienic practices. This included hand washing and an increased frequency of slaughters per day (>15,000).Conclusion: This study indicates that the water used for dressing chickens is probably the major cause of high levels of cross-contamination. The results also highlight the issues that need to be addressed to improve environmental and carcass hygiene in a poultry abattoir.Significance: Critical findings in this study are that contamination sources may be variable and hygienic practices may play a major role. In this particular study, the reuse of contaminated water was a case in point. Accordingly, there is need for both the water source and the water being used for processing to be tested.